2017
DOI: 10.1590/0001-3765201720150709
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and organic selenium for broilers from 22 to 42 days old: performance and carcass traits

Abstract: This study was conducted to evaluate the effect of vitamin E and selenium on performance, viability, productive efficiency, and yields of carcass, major cuts, and organs of broilers from 22 to 42 days submitted to cyclic-heat stress. The experimental design was randomized blocks, in a 2 × 3 factorial arrangement with two levels of selenium (0.1 and 0.3 mg/kg) and three levels of vitamin E (300, 400, and 500 mg/kg), plus a control treatment. Animals were submitted to a natural condition of high cyclic temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Supplementation of 200 mg/kg of Vit E in broiler diet improved weight gain and feed intake compared to the basal diet [ 39 ]. In contrast, dietary Vit E and Se had no effect on the body weight of layer hens [ 40 ], and different Vit E levels showed no significant changes in the broiler performance [ 41 ]. On the other hand, present study showed that both Se and Vit E supplementation had no significant effect on the lymphoid organ weights (thymus, bursa, and spleen) in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of 200 mg/kg of Vit E in broiler diet improved weight gain and feed intake compared to the basal diet [ 39 ]. In contrast, dietary Vit E and Se had no effect on the body weight of layer hens [ 40 ], and different Vit E levels showed no significant changes in the broiler performance [ 41 ]. On the other hand, present study showed that both Se and Vit E supplementation had no significant effect on the lymphoid organ weights (thymus, bursa, and spleen) in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding probiotics have been reported able to reduce fat content [ 12 ] as well as improve carcass traits of broiler chickens [ 13 ]. Certain vitamins, for example, tocopherol [ 14 , 15 ] and retinol [ 16 ] have also been reported to decrease the abdominal fat content and enhance carcass mass of broilers. Concomitantly, dietary supplementation with minerals such as Mn [ 17 , 18 ], Zn [ 16 ], and S [ 19 ] was beneficial to decrease the abdominal fat deposition in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…At cellular and biochemical level, ROS bind to biomolecules such as nucleic acid, lipids and proteins resulting in the production of oxidized products of the molecules e.g. guanosylated nucleic acids, carbonylated proteins, and peroxidized lipids (Albuquerque et al 2017). Among the oxidative stress markers, levels of lipid peroxidation and activities of antioxidant enzymes like catalase, superoxide dismutase, glutathione peroxidase etc.…”
Section: Discussionmentioning
confidence: 99%